Mechanistic insight into the displacement of CH4 by CO2 in calcite slit nanopores: the effect of competitive adsorption. Issue 106 (1st November 2016) - Sun, Haoyang; Zhao, Hui; Qi, Na; Qi, Xiaoqing; Zhang, Kai; Sun, Wenchao; Li, Ying
Abstract : Displacement of residual CH4 by CO2 in calcite slit nanopores owing to the competitive adsorption of CO2 over CH4 . Abstract : Grand Canonical Monte Carlo (GCMC) and molecular dynamics (MD) simulation methods were used to investigate the adsorption and diffusion properties of CH4 and CO2 in calcite slit nanopores with a pore width of ∼22 Å. It was found that, in contrast to CH4, CO2 molecules have a much higher capacity to be adsorbed onto calcite pore surfaces. The diffusion capacity of CO2 molecules is much less in comparison with that of CH4 molecules, which could be attributed to diverse interactions between CO2 gas molecules and calcite nanopore surfaces. An effective displacement process of residual adsorbed CH4 in calcite slit nanopores by CO2 was performed, and it was found that the displacement efficiency was enhanced with an increase in the bulk pressure. This work provides microscopic information about the adsorption and diffusion properties of CH4 and CO2 in calcite nanopores, and confirmed the feasibility of the displacement of adsorbed CH4 in calcite nanopores by CO2, with the purpose of providing useful guidance for enhancing the extraction of shale gas by injecting CO2 .